2022
DOI: 10.1038/s41467-022-28016-1
|View full text |Cite
|
Sign up to set email alerts
|

Nanobubbles explain the large slip observed on lubricant-infused surfaces

Abstract: Lubricant-infused surfaces hold promise to reduce the huge frictional drag that slows down the flow of fluids at microscales. We show that infused Teflon wrinkled surfaces induce an effective slip length 50 times larger than expected based on the presence of the lubricant alone. This effect is particularly striking as it occurs even when the infused lubricant’s viscosity is several times higher than that of the flowing liquid. Crucially, the slip length increases with increasing air content in the water but is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
63
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(78 citation statements)
references
References 57 publications
15
63
0
Order By: Relevance
“…Finally, although superhydrophobic surfaces have been extensively tested under conditions of flow (Table 5), only three studies have reported slip measurements in liquid‐infused surfaces using the pressure drop method (see Table 6 and ref. [ 26 ]).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Finally, although superhydrophobic surfaces have been extensively tested under conditions of flow (Table 5), only three studies have reported slip measurements in liquid‐infused surfaces using the pressure drop method (see Table 6 and ref. [ 26 ]).…”
Section: Discussionmentioning
confidence: 99%
“…Only three pressure drop measurements of slip have been reported so far on liquid‐infused surfaces as presented in Table 6 and ref. [ 26 ]. In these studies, the viscosity ratio between the working fluid and the infused liquid is a key factor in determining the effective slip provided by these surfaces.…”
Section: Theoretical Models and Experimental Measurements Of Slipmentioning
confidence: 99%
See 2 more Smart Citations
“…Understandings of in-droplet bubble formation may lay a foundation for exploring droplet reactions with enhanced chemical kinetics and hydrogen generation. Moreover, nanobubbles encapsulated in surface droplets may lead to a new pathway to functional slippery surfaces to reduce the surface friction, 45 porous surface-bound materials by templating nanobubbles, 46 or coated bubbles used in biomedical imaging, and therapeutic delivery of oxygen or other pharmaceutical compounds. 47,48 List of symbols Theoretical average growth rate of hydrogen bubbles nearing the droplet surface…”
Section: Discussionmentioning
confidence: 99%